(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The review considers the issues of adaptation of functional systems and regulation of homeostasis, which are characterized by their genetic determinism and phenotypic variability, universality and specificity. It has been established that, on the one hand, these processes determine, on the one hand, the complexity of the structure and meaning of a functional system, and, on the other hand, the unity of the structural and functional levels of the organization of a living being during adaptation and regulation of homeostasis.